Digital equity in mathematics education: Technology use in academic and vocational tracks - Hesty Ummi Wulandari; Farida Nurhasanah; Dhidhi Pambudi (Universitas Ahmad Dahlan, 2026)
Digital equity in mathematics education is shaped not only by the availability of devices but also by the quality and purposes of technology use in learning. This study maps how technology is used in mathematics learning across academic and vocational tracks and examines its implications for digital equity. A systematic literature review was conducted following PRISMA 2020 guidelines using the Scopus database, covering publications from 2015 to 2025. A total of 44 selected articles were analyzed through descriptive mapping and thematic analysis to identify technology categories and patterns of use in both tracks. The findings show a clear divide: in the academic track, technology is more often used as cognitive tools to support visualization, conceptual exploration, and higherorder learning. In contrast, in the vocational track, technology is more commonly used for communication, learning management, and strengthening basic skills or remediation. In addition, the evidence base is concentrated in developed countries, while studies focusing on vocational tracks and developingcountry contexts, including Indonesia, remain limited. These results highlight a gap that may reduce vocational students’ learning opportunities. Future research should expand evidence from vocational settings and developing countries, while policy should strengthen pedagogical support so that technology use in vocational education also promotes conceptual understanding and mathematical reasoning.